An Association between Single Nucleotide Polymorphisms of Lys751Gln ERCC2 Gene and Ovarian Cancer in Polish Women. (7th October 2015) - Michalska, Magdalena M.; Samulak, Dariusz; Romanowicz, Hanna; Sobkowski, Maciej; Smolarz, Beata
Abstract : Aim. The aim of this study was to evaluate the role of the Lys751Gln (rs13181) ERCC2 gene polymorphism in clinical parameters and the risk for development of ovarian cancer. Material and Methods. The study consisted of 430 patients with ovarian cancer (mean age: 53.2 ± 10.11) and 430 healthy subjects (mean age: 50.31 ± 18.21). Analysis of the gene polymorphisms was performed using the PCR-based restriction fragment length polymorphism (PCR-RFLP). The odds ratios (ORs) and 95% confidence intervals (CIs) for each genotype and allele were calculated. Results. The results obtained indicate that the genotype Gln/Gln is associated with an increased risk of ovarian cancer (OR 5.01; 95% CI 3.37–7.43;p < 0. 0001 ). Association of Lys751Gln polymorphism with histological grading showed increased ERCC2 Gln/Gln (OR = 6.96; 95% CI 3.41–14.21;p < 0. 0001 ) genotype in grading 1 as well as Gln allele overrepresentation (OR = 4.98; 95% CI 3.37–7.40;p < 0. 0001 ) in G1 ovarian patients. Finally, with clinical FIGO staging under evaluation, an increase in ERCC2 Gln/Gln homozygote frequencies in staging I and Gln allele frequencies in SI were observed. Conclusion. On the basis of these results, we conclude that ERCC2 gene polymorphism Lys751Gln may be associated with an increased risk of ovarian carcinoma.